Effect of Strength Training on Rate of Force Development in Older Women - Demantova Gurjao, Andre Luiz [UNESP]; Bucken Gobbi, Lilian Teresa [UNESP]; Cameiro, Nelson Hilario; Goncalves, Raquel [UNESP]; de Moura, Rodrigo Ferreira; Cyrino, Edilson Serpeloni; Altimari, Leandro Ricardo; Gobbi, Sebastiao [UNESP] (Amer Alliance Health Phys Educ Rec & Dance, 2012)
We analyzed the effect of an 8-week strength training (ST) program on the rate of farce development (RFD) and electromyographic activity (EMG) in older women. Seventeen women (M age = 63.4 years, SD = 4.9) without previous ST experience were randomly assigned to either a control (n = 7) or training (n = 10) group. A leg-press isometric test was used for assessment. ST (three sessions/week, three sets of 10-12 repetition maximum, five different exercises) induced significant increases (p < .05) on peak RFD (48.4%) and on RID and EMG of vastus medialis at time intervals of 0-50, 0-100, 0-150, and 0-200 ms (41.1-69.2% and 43.8-64.3 %, respectively). Therefore, ST resulted in favorable changes in neuromuscular responses in older women.
Keywords: aging; muscle activation; neuromuscular performance; resistance training